Evaluación de niveles de fertilización en pasto janeiro (Erioclhoa polystachya) irradiado a 52 Gy bajo las condiciones edafoclimáticas del cantón Babahoyo - Paucar Castro, José Olmedo (2020)
This research work was carried out on the premises of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at km. 7.5 of the Babahoyo-Montalvo road. The geographical coordinates in UTM were X: 1,7723946; Y: 79.7102593. The area has a humid tropical climate, with a temperature that ranges between 24 and 26 ° C, with relative humidity of 88%, average annual rainfall of 1262 mm, with a height of 8 meters above sea level and 990 hours of annual average heliophany. As evaluation material, weed plants were used, from the material irradiated at 52 Gy of gamma rays (60 Co). In this investigation, a "Random Complete Blocks" Design was used, with five treatments and four repetitions, the variables evaluated were: plant length, leaf length, leaf width, leaf area, stem diameter, number of leaves , wet weight yield, dry weight yield, dry matter yield percentage (RMS). In the present investigation it was possible to determine what the fertilization dose applied in the T3 treatment (Urea 300 Kg / ha) showed highly significant statistical differences in number of leaves, wet weight and dry weight with respect to T5 (0 Kg / ha) that was the control with dose 0. With respect to the agronomic variables: leaf width, stem diameter, percentage of dry matter yield, they did not present statistical significance and the results show that the T5 treatment (0 Kg / ha presented numerically the lowest Averages Numerically the treatment T3 (Urea 300 Kg / ha) surpasses all the treatments in the variables plant length, leaf length, leaf area.